Cross-border effectiveness of judicial decisions assisted by artificial intelligence in the European Judicial Area - López Rodríguez, Ana Mercedes (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The increasing integration of algorithmic systems into judicial processes, as tools to assist decision-making, has raised questions about their compatibility with fundamental principles of Private International Law, such as transparency, due process, and international public policy. The present article analyzes key issues in this context, including the need to harmonize international standards on algorithmic transparency and technical certification, the limits of public policy in relation to automated decisions, and the transformation of the normative framework to ensure legal certainty in a globalized environment. Finally, the article proposes recommendations for developing a regulatory framework that integrates technological innovation into justice systems without compromising essential principles of PIL. This analysis aims to contribute to the debate on how to balance technological efficiency with legal safeguards in the cross-border recognition of AI-assisted judicial decisions